E-Project Based Learning Using Animation For Primary School Students - Mohd Yusof, Anuar (2010)
The paper was the exploratory study on the project based learning activities with the blended learning environment in the classroom from primary school\'s student. The study highlight the users\' perception on the eProjBL which might be promoting the new learning environment in Malaysia.